The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/iub.398
|View full text |Cite
|
Sign up to set email alerts
|

Increased female fertility in aquaporin 8‐deficient mice

Abstract: SummaryAquaporin-8 (AQP8) is a water channel expressed extensively in male and female reproductive systems. But its physiological functions are largely unknown. In the present study, we first found significantly increased number of offspring delivered by AQP8 2/2 mothers compared with wild-type mothers in crossmating experiments. Comparison of ovulation in the two genotypes demonstrated that AQP8 2/2 ovaries released more oocytes (9.5 6 1.9 vs. 7.1 6 2.1 in normal ovulation and 37.8 6 6.7 vs. 27.9 6 5.7 in sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 27 publications
4
36
1
Order By: Relevance
“…In the reproductive system, AQP8 is strongly expressed in the testis and sperm in the male and in the ovary, oviduct, uterus, placenta, amnion, chorion and cervix in the female [16][17][18][19][20][21][22][23][24][25] . While an earlier study [26] of AQP8 null mice reported no significant differences in comparison to wild type controls with the exceptions of an increase in testicular volume and a reduction in water permeability within the testes, we observed that AQP8 deficiency increased the number of mature follicles and the resulting fertility of female mice [27] . The present study aims to survey the role of AQP8 during pregnancy in AQP8-KO mice.…”
Section: Introductioncontrasting
confidence: 92%
See 4 more Smart Citations
“…In the reproductive system, AQP8 is strongly expressed in the testis and sperm in the male and in the ovary, oviduct, uterus, placenta, amnion, chorion and cervix in the female [16][17][18][19][20][21][22][23][24][25] . While an earlier study [26] of AQP8 null mice reported no significant differences in comparison to wild type controls with the exceptions of an increase in testicular volume and a reduction in water permeability within the testes, we observed that AQP8 deficiency increased the number of mature follicles and the resulting fertility of female mice [27] . The present study aims to survey the role of AQP8 during pregnancy in AQP8-KO mice.…”
Section: Introductioncontrasting
confidence: 92%
“…Furthermore, while embryo number progressively decreased with advancing gestational age in both groups, embryo number was greater in the AQP8-KO group compared to wild type, with a comparable incidence of atrophic embryos. These results may be associated with an increase in follicular maturation and ovulation, as an increase in corpus luteum number has previously been reported in mature AQP8-KO ovaries [27] .…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations